2000
DOI: 10.1128/aac.44.12.3465-3472.2000
|View full text |Cite
|
Sign up to set email alerts
|

Differential Removal of Thymidine Nucleotide Analogues from Blocked DNA Chains by Human Immunodeficiency Virus Reverse Transcriptase in the Presence of Physiological Concentrations of 2′-Deoxynucleoside Triphosphates

Abstract: Removal of 2,3-didehydro-3-deoxythymidine-5-monophosphate (d4TMP) from a blocked DNA chain can occur through transfer of the chain-terminating residue to a nucleotide acceptor by human immunodeficiency virus type 1 (HIV-1) reverse transcriptase (RT). ATP-dependent removal of either d4TMP or 3-azido-3-deoxythymidine-5-monophosphate (AZTMP) is increased in AZT resistant HIV-1 RT (containing D67N/K70R/ T215F/K219Q mutations). Removal of d4TMP is strongly inhibited by the next complementary deoxynucleoside triphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
119
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(130 citation statements)
references
References 36 publications
(45 reference statements)
11
119
0
Order By: Relevance
“…We then compared the initiation and elongation steps of (Ϫ) strand DNA synthesis. The results we obtained using a DNA template and a DNA primer are consistent with previous studies (21)(22)(23)36). They show that the mutant RT harboring mutations D67N, K70R, T215F, and K219K can efficiently repair an AZT-terminated DNA primer in the presence of 3.5 mM ATP.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…We then compared the initiation and elongation steps of (Ϫ) strand DNA synthesis. The results we obtained using a DNA template and a DNA primer are consistent with previous studies (21)(22)(23)36). They show that the mutant RT harboring mutations D67N, K70R, T215F, and K219K can efficiently repair an AZT-terminated DNA primer in the presence of 3.5 mM ATP.…”
Section: Discussionsupporting
confidence: 81%
“…2B). Because ATP lysis was much slower than nucleotide addition to the 3Ј-end of an unblocked primer (30), our results suggest that ATP lysis was partially inhibited by the next incoming nucleotide (22,36). The rescue of DNA synthesis was observed with the wt RT in the presence of ATP and with resistant RT in its absence, but these reactions were too weak to allow quantitative analysis (Fig.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…In this instance, a pyrophosphate donor, such as ATP, can excise the nucleotide analogue, providing an important mechanism for resistance. Mutations in HIV-1 RT that confer resistance to the NRTI, 3Ј-azidothymidine, increase rates of excision (15)(16)(17)(18)(19)(20)(21). More recently, it has been shown that mutations in the connection and RNase H domains of HIV-1 RT confer resistance to NRTIs and NNRTIs (9,10,(22)(23)(24)(25)(26).…”
Section: Hiv-1mentioning
confidence: 99%